Variability of wave parameters and Hmax/Hs relationship under storm conditions offshore the Portuguese continental coast. (1st April 2018) - Oliveira, Tiago C.A.; Neves, Maria Graça; Fidalgo, Raquel; Esteves, Rita
Abstract: The relevance of long-term wave storm characterization based on in-situ measurements extends from marine ecosystems management to the design of ocean engineering structures. We analyze wave storms recorded over almost three decades (1988–2015) in three points offshore the Portuguese continental coast located between 83 and 97 m water depth. We provide Probability Distribution Functions for mean wave direction ( θ m ), directional wave spreading ( σ θ ), significant wave height ( H s ), maximum wave height ( H max ), mean wave period ( T z ) and, H max / H s relationship based on four storm datasets. In the highly energetic Portuguese west coast (Leixões and Sines), H max and H max / H s ranged between 5.5 and 17.3 m and 1.16 to 2.47, respectively. We conclude that a GEV distribution can represent H max and H max / H s variability at the three analyzed locations. Despite the differences in the dataset lengths and the differences in the range and variability of θ m, σ θ, T z, H s, and H max, we found that the range and variability of H m a x / H s are very similar for the four storm datasets. For the analyzed period, σ θ ranged between 8 and 52° and 10 to 59° in the west and south coast (Faro Atlantic and Faro Levante storms), respectively, and its variability can be described by a log-logistic distribution. Highlights: Long-term wave storm characterization based on in-situ measurements. PDFs for the variability of H s, H max, θ m, σ θ, T z and H max / H s under storm conditions are presented. The dependence of H max / H s on H s, H max, θ m, σ θ, and T z is analyzed. 10% of storm sea states presented an H max / H s > 1.83 offshore the Portuguese west coast.